Midterm outcomes of mini-invasive surgical and hybrid ablation of atrial fibrillation - Pojar, Marek; Haman, Ludek; Parizek, Petr; Myjavec, Andrej; Gofus, Jan; Vojacek, Jan (Biomedical papers, 2019)
Background: We evaluated the feasibility and effectiveness of thoracoscopic and a staged surgical and transcatheter ablation technique to treat stand-alone atrial fibrillation (AF). Methods: . Between 2009 and 2016, a cohort of 65 patients underwent bilateral totally thoracoscopic ablation of symptomatic paroxysmal AF (n=30; 46%), persistent AF (n=18; 28%) or long-standing persistent AF (n=17; 26%) followed by catheter ablation in case of AF recurrence. Surgical box lesion procedure included bilateral pulmonary vein and left atrial posterior wall ablation using irrigated bipolar radiofrequency with documentation of conduction block. Results: There were no intra- or peri-operative ablation-related complications. There was no operative mortality, no myocardial infarction, and no stroke. Skin-to-skin procedure time was 120.5 ± 22.0 min and the postoperative average length of stay was 8.1 ± 3.0 days. At discharge, 60 patients (92%) were in sinus rhythm. Median follow-up time was 866 days (IQR, 612-1185 days). One-year success rate after surgical procedure was 78% (off antiarrhythmic drugs). Eleven patients (17%) underwent catheter re-ablation. Sixty (92%) patients were free of atrial fibrillation after hybrid ablation (on demand) at 1 year follow up after the last ablation. The success at 24-months was achieved in 96% (paroxysmal) and 78% (persistent) patients. At the last follow-up control, 69% patients discontinued oral anticoagulant therapy. Conclusions: . Combination of mini-invasive surgical and endocardial treatment (two-stage hybrid procedure) is a safe and effective method for the treatment of isolated (lone) AF. This procedure provided good midterm outcomes.
Keywords: atrial fibrillation; thoracoscopic ablation; hybrid ablation